Seroprevalence and Risk Factors of Hepatitis B Virus Among Newly Diagnosed Cancer Patients in Khartoum State: Implications for Chemotherapy Management and Screening Protocols - Anwaar Abdulgader Merghani Alkhdir; Abubaker A. Mohamedsharif; Isra Bdraldein Salih Mohammed; Amin Mohamed Abbas (JGH Open)
ABSTRACT Aims This study aimed to determine the seroprevalence of hepatitis B virus (HBV) among newly diagnosed cancer patients in Khartoum State, Sudan, prior to chemotherapy initiation and to identify associated risk factors. Methods and Results A cross‐sectional study was conducted from October 2022 to April 2023 at various oncology centers in Khartoum State. A total of 300 newly diagnosed cancer patients, aged 18 years and older, were included. Blood samples were screened for Hepatitis B surface antigen (HBsAg) using a rapid immunochromatographic test (ICT) and confirmed by enzyme‐linked immunosorbent assay (ELISA). The study found that 31 patients (10.3%) were HBsAg positive. A significant association was observed between HBV positivity and patients' history of blood transfusions (41.9% of positive cases), as well as geographic origin, with higher rates among those from Western Sudan (44.7%) and Central Sudan (40.6%). Patients diagnosed with hematological malignancies exhibited the highest HBV prevalence. Statistical analysis revealed significant correlations between HBV positivity and factors such as age, gender, residence, and transfusion history, indicating these as key risk factors. Conclusion The study reveals a notable HBV seroprevalence among cancer patients in Khartoum, particularly linked to blood transfusion history and specific regions. These findings emphasize the need for routine HBV screening in oncology patients before chemotherapy to prevent reactivation and improve clinical outcomes.